Call for Social Justice in Arvind Adiga’s The White Tiger - Baral, Pawan (NUTA Journal, 2021)
The paper aims at examining Arvind Adiga’s The White Tiger in the light of social justice under the then political establishments of India where globalization has almost paralyzed the heart of democracy itself. Adiga deploys many techniques to intensify his arguments, the amalgamation of which has a magic-like emphatic effect in his expression of bitterness. He mixes up lightheartedness, extremity of injustice, IT age version of epistolary mode, and playful colloquial language in such a way it hypnotizes the readers from suspecting frequent exaggerations of situations and lack of authenticity in his depiction. The paper ultimately argues that Adiga calls for a just society through the novel. He feels ashamed of the contemporary democratic practice which may produce many, many Balrams unless the system of government restores social justice in time. With strong conviction on democracy as a good system of government, Adiga leaves a note of optimism amid confusion and hopelessness. As a staunch democrat, he has two ways of reformation in the present practice in the final chapter: the first for the short-run and the other for the long-run. Ultimately, Adiga envisions that enlightened citizenry can contribute to the free and fair practice of democracy and of globalization in the long run. The study adopts qualitative based literary mode of research. It draws primary data through close reading of the text in question. Then the firsthand data from the text will be analyzed drawing and departing the ideas of critics and thinkers of social justice, globalization and democracy as well as.